Farmers’ market: consumer trends, taste, preferences, and characteristics towards buying value added products directly from producer - Gayathri, S; Vikraman, A; Vinuchakravarthi, V; Srinivasan , S (Journal of Postharvest Technology, 2023)
Farmers Markets gaining momentum these days, consumers are turning to food festivals, Farmers Market and agritourism expecting to get  fresh foods other than regular market. Today these platforms help farmer’s particularly organic farmers who aim to add value to the produce  and directly sell to the consumer. This paper is to attempt the consumer trends, preferences and characteristics towards buying value  additions directly from producer. Sample of 360 respondents were collected from consumer through random sampling method and results  show that availability of fresh products and satisfaction of buying directly from buyers are some of the influencers for consumers, Organic Rice  products, Millets, oil and Dairy products are some of the products which have good reception among consumers in Farmers market.
Keywords: Food festival; farmers market,; organic farming ,; traditional rice; direct selling; farm fresh.